Pembinaan Komunikasi Efektif Bagi Kader Dalam Layanan Bina Keluarga Balita (BKB) Kampung Indra Putra Subing Provinsi Lampung - Lovia Evanne; Leti Karmila; Agus Srimudin; Herdiansyah Amanu (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
Cadres are volunteers who are at the forefront of the Bina Keluarga Balita (BKB) service. Bina Keluarga Balita (BKB) cadres must be able to communicate and motivate parents to be responsible for children's growth and development. One of the BKKBN policy directions contained in the 2015-2019 BKKBN Renstra is a policy to increase family development regarding parents' understanding of the importance of families in caring for toddler and child development. The implementation of government policies to improve the quality of children in the context of family development is carried out through Bina Keluarga Balita (BKB) which aims to increase the knowledge and skills of parents to nurture and foster children's growth and development through physical, mental, intellectual, emotional, spiritual, social and moral stimulation activities. Based on this situation, it is considered important to provide seminars to cadres in the Bina Keluarga Balita (BKB) service regarding knowledge about the effectiveness of communication which will provide information to parents of toddlers. The role of cadres in Bina Keluarga Balita (BKB) services is very strategic in order to achieve healthy and quality toddlers.